Giorgio Agamben's Form of Life. (3rd April 2017) - Hunter, Ian
ABSTRACT: Giorgio Agamben's discourse on Franciscan monasticism is generally received in accordance with his presentation of it: as a genealogy or archaeology of the way in which the Franciscans were the first to embody an exemplary form of life. This paper offers a different view, arguing that Agamben's account of the Franciscans is actually an allegory whose underlying structure and meaning is supplied by Heideggerian metaphysics. One of the striking features of Agamben's discourse is that it treats actual historical events as allegorical symbols or 'paradigms' of a hidden metaphysical reality whose decipherment both clarifies the past and reveals the future. It is shown that this exemplary way of viewing historical events is embedded in a specialized spiritual exercise. Here, allegorical writing and reading act as practices of self-transformation that promise exalted insight into the hidden meaning of historical 'paradigms' regardless of historical scholarship.